Performance Assessment in the Final Semester Examination for Violin Instrument Studies Music Education Study Program Indonesian Institute of The Art Yogyakarta - Adzkia, Sagaf Faozata (LPPM Institut Seni Indonesia Padangpanjang, 2024)
Violin instrument practicum at the ISI Yogyakarta Music Education Study Program is included in the Instrument Studies course in 4 levels, consisting of Instrument Studies I, II, III, and IV. In the assessment of the final semester exam for this course, the assessment is carried out using the idea of performance assessment which is applicable to the characteristics of violin performance, to avoid assessment bias. This article is the result of qualitative research with the material object of implementing the Final Semester Examination/UAS for the violin instrument study course at the ISI Yogyakarta Music Education Study Program, and the formal object of performance assessment in terms of the musicological aspect. The stages taken in this research include the process of literature study, observation, interviews and analysis. The result in this article is that performance assessment is needed as an accuracy of assessment parameters. The expected goal is that lecturers and students can use the evaluation results from performance assessments as a guide to identifying strengths and weaknesses in violin playing skills. Assessment includes: fundamental aspects include assessing the close relationship between the player's body posture and the violin instrument; aspects of notation and intonation accuracy; aspects of rhythmic accuracy; and aspects of musical interpretation.